Road Connectivity and the Border Effect Evidence from Europe - Braconier, Henrik (OECD Economics Department Working Papers, 2013)
Several studies have reported a large negative effect of national borders on the volume of trade. We provide new estimates of the border effect for continental Europe using road rather than great circle - or "as-crows-fly" - distance. Road distances for 48 180 European city pairs have been extracted from Bing Maps Routing Services. As our dataset also has information on travel time, we are able to consider costs related to time in addition to those depending on distance. We find that for the same great circle distance and the same city size, the road distance between two cities located in the same country is around 10% shorter than that between cities located in different ones. Travel speed is also higher between cities in the same country. We find that by using measures based on the actual road distance rather than the great circle distance, the negative effect of international borders on goods trade in a standard gravity equation is lowered by around 15%. Time-related trade costs account for an additional 10% reduction in the border effect. Overall these results point to the importance of road networks - and road transport policy in general - to enhance market integration